A peaceful solution to the nuclear tension in the Korean peninsula (2020)
In spite of the efforts of the international community to solve the Democratic People’s Republic of Korea (DPRK) nuclear crisis, this issue remains unsolved. The relevance of this matter lies in the need to find a permanent solution to the crisis that leads to a total denuclearization of the Korean Peninsula. Therefore, the aim of this article is to demonstrate the need of a peaceful solution to the DPRK nuclear issue in which the security concerns of North Korea are addressed by signing a peace treaty with Pyongyang that ensures that the United States will not attack the regime, will remove its troops from South Korea and will finish its military drills with this ally. This article will discuss what elements will be necessary to achieve a peaceful solution to this nuclear conundrum.